Defence rights in European Union Law - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Since mutual recognition of decisions in criminal proceedings, as the basis for international cooperation in criminal matters in the European Union, is unthinkable without mutual trust between the member states, and mutual trust is inextricably linked to the state’s belief that its citizens are protected in another Member State, in the sense that they are guaranteed the same level of protection of basic procedural rights in criminal proceedings, it became clear and possible, after the entry into force of the Lisbon Treaty on the European Union, that it is necessary to regulate the procedural rights of the defendant at the supranational level. The individual rights of the defendant in criminal proceedings, as elements of the right to defense, are governed in the law of the European Union by a set of directives that have been adopted with the aim of strengthening procedural guarantees of the right to defense by imposing minimum rules.